Wren Macdonald: capstone - Macdonald, Wren, artist (Colorado State University. Libraries, 2021)
The artist's statement: I have been searching for a sort of quietness in my work, like that of a person-less forest, or of a small beetle crawling across soil, or of a wary deer - because I think my mind is most often loud and troubled with thought. Perhaps this is why I choose to construct animal bodies frequently. They are good at being without existential anxiety. I make work that urges a form of attention attuned to overlooked details. Minutiae, both tangible and intangible, are boundless and wonder opens a space in which beings interact and collaborate. I work towards trusting the intelligence of objects to accumulate a kind of unfolding vastness within their intimacy. Ideas strike me that cannot be explained, so I must make them, in a physical form, and let the work speak. I think many artists do this; let the work speak. The intersection between illustration and sculpture is intuitive and immensely important; a single rabbit can constitute a muffled shrubscape, in its absoluteness. I think through illustration; through an abundance of detail, a space of and beyond the given picture plane opens.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery